Allele specific-PCR and melting curve analysis showed relatively high frequency of Î²-casein gene A1 allele in Iranian Holstein, Simmental and native cows - Gholami, M.; Hafezian, S. H.; Rahimi, G.; Farhadi, A.; Rahimi, Z.; Kahrizi, D.; Kiani, S.; Karim, H.; Vaziri, S.; Muhammadi, S.; Veisi, F.; Ghadiri, K.; et al. (Cellular and Molecular Biology, 2016)
There are two allelic forms of A1 and A2 of Î²-casein gene in dairy cattle. Proteolytic digestion of bovine Î²-casein A1 type produces bioactive peptide of Î²-casomorphin-7 known as milk devil. Î²-casomorphin-7 causes many diseases, including type 1 diabetes, cardiovascular disease syndrome, sudden death and madness. The aim of the present study was to determine the different allelic forms of Î²-casein gene in Iranian Holstein, Simmental and native cattle in order to identify A1 and A2 variants. The blood samples were collected randomly and DNA was extracted using modified salting out method. An 854 bp fragment including part of exon 7 and part of intron 6 of Î²-casein gene was amplified by allele specific polymerase chain reaction (AS-PCR). Also, the accuracy of AS-PCR genotyping has been confirmed by melting temperature curve analysis using Real-time PCR machinery. The comparison of observed allele and genotype frequency among the studied breeds was performed using the Fisher exact and Chi-squared test, respectively by SAS program. Obtained results showed the A1 allele frequencies of 50, 51.57, 54.5, 49.4 and 46.6% in Holstein, Simmental, Sistani, Taleshi and Mazandarani cattle populations, respectively. The chi-square test was shown that no any populations were in Hardy-Weinberg equilibrium for studied marker locus. Comparison and analysis of the test results for allelic frequency showed no any significant differences between breeds (P>0.05). The frequency of observed genotypes only differs significantly between Holstein and Taleshi breeds but no any statistically significant differences were found for other breeds (P>0.05). A relatively high frequency of Î²-casein A1 allele was observed in Iranian native cattle. Therefore, determine the genotypes and preference alleles A2 in these native and commercial cattle is recommended.